Optimalisasi Bank Sampah sebagai Solusi Pemberdayaan Masyarakat Kelurahan Gunung Anyar Tambak Kota Surabaya - Rahmawati Rahmawati; Wirna Amalia (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
The 2023 Surabaya City Waste Bank Competition, which was opened by the Mayor of Surabaya himself, included many villages that placed first, including Gunung Anyar Tambak Village. The government and local community of Gunung Anyar Tambak Village, Surabaya, have taken an ecologically conscious approach to solving the garbage issue via the garbage Bank Program. Reducing trash sent to the TPA (Final Disposal Area) and raising public awareness about the need for proper waste management are the primary goals of this campaign. Located in the Mangrove region, Gunung Anyar Tambak Village lies on the seashore. The researcher use a qualitative descriptive methodology, gathering data via interviews, documentation, and observation. Data collecting takes done at the research site. An individual's capacity to influence their own social, economic, and political circumstances is crucial to their advancement in society, and community empowerment provides that opportunity. In order to address waste issues and use available resources, the trash bank program was developed as a community and environmental empowerment initiative. An individual's capacity to influence their own social, economic, and political circumstances is crucial to their advancement in society, and community empowerment provides that opportunity. The Bintang Mangrove trash bank offers a variety of community empowerment activities, including as savings and loans, power payment, medical treatment, recycling, replanting, and environmental care.